Hub-and-spoke arrangement under the competition Act 2010 - Aiman Danial Dazuki; Lim, Chin Lun (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
This paper aims to briefly discuss what is hub and spoke arrangement and inasmuch it is can be said to infringe competition law regime. Hub and spoke remain prevalent as of now due to its complexity and significant anti-competitive effect posed by such arrangement. Plus,there is no solid measure in addressing this arrangement and the intertwined relationship between the entities makes it difficult for attribution of liability. Malaysian competition law regime is relatively new in the game by comparing to EU and UK competition law regimes. Even the aforementioned jurisdictions have not provided a clear guide to address hub and spoke arrangement. Throughout MyCC’s decisions, it appears that hub and spoke arrangement has its foundation in Malaysia. Further, the hub or in form of trade associations and upstream players, in the context of MyCC’s decision, always escaped from financial penalty regardless of active participation. The imposition of a symbolic fine seems to be unfavorable to MyCC when it comes to fining those who indirectly participate. This paper illustrates how the hub and spoke arrangement can instil anti-competitive conduct specifically in time with the rapid growth of digitalisation which discreetly becomes the hub. Thus, this paper provides two start-ups in considering for hub and spoke cases with reference to EU and UK approaches. Then, this paper wishes to caution that, EU and UK competition law regimes are different from the Malaysian which do not warrant for direct transplantation of aforesaid jurisdictions to Malaysian Competition Act 2010 due to some substantial differences. Having said all, this paper aims to clarify the question that Competition Act 2010 pursuant to section 4 provides a separate tier of agreement as it can only be either horizontal or vertical agreement.